Adaptability of two species of Lupinus in different environments of the high inter-Andean valleys from Bolivia - Juan Vallejos Arnéz; Pablo Mamani Rojas; Javier Huiza Nina; Julio Gabriel-Ortega (Journal of the Selva Andina Biosphere)
With the objective of evaluating the adaptation of two two new species of Lupinus cultivars (Lupinus angustifolius and Lupinus albus) to the inter-Andean highland valleys of Bolivia, the two mentioned species were evaluated for five years (agricultural seasons 2015-2019) in the high Andean valleys from Bolivia. The evaluations were carried out in five municipalities of Cochabamba and one in Potosí. Through the five years of evaluation, 36 plots from Chejchita and 18 from Jatunta were implemented in Cochabamba. In Potosí, 70 Chejchita plots and five Jatunta plots were implemented. To determine the yield, samples of 1 m2 per plot of each cultivar, and 4 to 20 samples were made per plot. The plots were implemented under a completely randomized block design with sub-samplings, where the blocks were the localities. Analysis of variance was performed to determine the fixed and random effects using an analysis of serial experiments. The comparison of means was performed using the Tukey test at P <0.05 probability. Likewise, the genotype x environment interaction was analyzed to determine the behavior of each species in each zone. The results showed that in all localities, the Jatunta cultivar was superior in yield. The highest yield was obtained in Colomi for both species; likewise, Chejchita had a different behavior in each locality, while Jatunta looks for better environments to show its performance potential. Based on environment genotype x environment yield analysis, Chejchita showed a stable behavior in all the evaluated localities; however, the stability was not consistent. On the other hand, Jatunta had higher yields in favorable environments, contrary to unfavorable environments, the Jatunta variety had lower yields than Chejchita.